Tingkat Kematangan Implementasi Scrum Menggunakan Scrum Maturity Model Pada Direktorat TSI - Meynar Dwi Anggraeny; Anna Kurniawati; Dina Anggraini (G-Tech: Jurnal Teknologi Terapan, 2024)
Direktorat TSI is a unit that has the task of developing information systems. Since mid-2021, Direktorat TSI has adopted scrum in application system development that works iteratively and gradually until it reaches the needs desired by consumers. Scrum implementation provides improvements in the development of application systems in Direktorat TSI. However, there are still projects whose completion is late, the sprint backlog is incomplete, or the product backlog is incomplete. This study aims to analyze the maturity level of scrum implementation at this unit using the Scrum Maturity Model. The study uses a quantitative method of questionnaires with respondents from the Scrum Master on the FocusPN Project, the State Receivables Project, and the Auction Project. The results of the study show that the level of scrum implementation maturity in the FocusPN Project and State Receivables Project is still at Level 1 (Initial), while the Auction Project has reached Level 2 (Defined). Overall, the KPA Rating average shows that the TSI Directorate is still at level 1 (Initial).